The Link Between Pregnant Women’s Knowledge of Obstetric Danger Singns and Proactive Emergency Detection - Ni Gusti Made Ayu Agung Budhi; Karningsih Karningsih; Sri Sukamti; Mardeyanti Mardeyanti (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Despite global efforts, maternal mortality remains a critical public health challenge. A major contributing factor is the delay in recognizing and responding to obstetric emergencies. A pregnant woman's awareness of potential danger signs and her subsequent proactive attitude toward early detection are considered pivotal in facilitating timely and life-saving healthcare access. This study was undertaken to investigate the direct correlation between the level of knowledge pregnant women possess regarding pregnancy danger signs and their attitude toward the early identification of maternal emergencies.This research utilized an analytic survey design, a cross-sectional approach. The study sample was drawn using accidental sampling, comprising 110 pregnant women. Data were collected via structured questionnaires and analyzed statistically using the Spearman Rank correlation test. The descriptive analysis revealed a positive outcome regarding knowledge: the majority of participants (70) demonstrated a sufficient level of knowledge about pregnancy danger signs. However, this did not translate into a desired behavioral disposition, as a majority of participants (40) simultaneously displayed a poor attitude toward the early detection of maternal emergencies. The inferential statistical analysis confirmed this disconnect: the Spearman Rank test yielded a calculated ρ-value (pcount) of 0.068, which was less significant than the critical ρ-table value (ptable) of 0.364. Crucially, the significance level(p=0.72) exceeded the predetermined alpha (α=0.05).The study concludes that there is no significant relationship between a pregnant woman's knowledge of obstetric danger signs and her attitude toward seeking the early detection of maternal emergencies.